Development of High Print Image Media as a Source Learn on the Beautiful Theme of My Country - Sopiani, Resa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2020)
The aim of this research is to develop teaching material products in the form of image media high print as a learning resource on the theme of the beauty of my country sub theme diversity of animals and plants in the art is subject about steps to make high print images, mathematics which is about adding decimal parts and civics, namely explaining the benefits of animals and plants in high print images. This type of research is development research using ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research produces highly printed images as learning resources which can facilitate students to play an active role, as well as provide convenience for students to understand the concept of subject matter. Based on the research results obtained, (1) questionnaire results from learning experts 85% (Very good), questionnaire results from Image Media experts 78% (Good) validated by experts, the researchers tested it on 6 class IV students Elementary School with an interview method where the results are that each student has a response positive. This research has produced a teaching material product in the form of image media high print as a learning resource on the theme of the beauty of my country that can be facilitate students to play a more active role in the learning process, as well as make it easier for students to understand the concepts of the subject matter.